Effects of Biotin-Avidin Interactions on Hydrogel Swelling - Alina, Talaial B.; Nash, Victoria A.; Spiller, Kara L. (Frontiers in Chemistry, 2020)
Affinity interactions between the small molecule biotin and the protein avidin have been used extensively to functionalize biomaterials. More recently, researchers have leveraged the changes in biotin-avidin affinity that occur upon biotin conjugation to larger molecules to control the release of biotinylated drugs and proteins. However, the effects of biotin-avidin interactions on hydrogel properties have not been thoroughly investigated. The objective of this study was to evaluate the effect of increasing biotin and avidin concentrations on hydrogel swelling properties, as an indicator of crosslinking. Gelatin, selected as a model hydrogel material, was biotinylated at increasing fold molar excesses of biotin with a PEG linker using N-hydroxysuccinimide chemistry. Afterwards, biotinylated gelatin was formed into hydrogels and stabilized with glutaraldehyde. Swelling properties of the biotinylated hydrogels were investigated by conducting swelling studies in different avidin solutions. Increasing the degree of biotinylation caused significant decreases in swelling ratios of the hydrogels in a dose-dependent manner, suggesting increases in crosslinking of the hydrogels. However, increasing avidin concentrations in excess of biotin content did not significantly affect swelling ratios. Moving hydrogels to phosphate-buffered saline following avidin incorporation resulted in increased swelling ratios for hydrogels prepared with a lower concentration of biotin. However, hydrogels prepared with the highest concentration of biotin did not experience increased swelling ratios, implying that the stability of biotin-avidin-mediated crosslinking depends on the number of biotin molecules available for binding. Collectively, these results demonstrate that biotin-avidin interactions control hydrogel swelling properties, and that the magnitude and stability of the effects depend on the biotin concentration. These results have important implications for affinity-based controlled release of biotinylated drugs or proteins from biotin-avidin-crosslinked hydrogels.